Journal of international business disciplines
"Journal of International Business Disciplines encourages and supports scholarly works that focus on theories, research, and applications regarding topics related to business and organizations including but not limited to: accounting, advertising, communication, economics, diversity, globalization, groups, teams, finance, human resources, information technology, leadership, management, marketing, operations, and organizational behavior/theory."--About JIBD page